Classical waqf, juristic analogy and framework of awqāf doctrines - Mohammad Abdullah (ISRA International Journal of Islamic Finance, 2020)
Purpose: This paper aims to analyse the Sharīʿah premises of waqf (Islamic endowment), followed by dilating on the nature of argumentation among the classical jurists on its rules and principles. The paper critically analyses the edifice of the applied juristic analogy of different early jurists in deriving various waqf doctrines. The objective of analysing the jurisprudential framework of waqf in its classical mould is to conceptualise the methods, mechanism and nature of juristic analogies in deriving the waqf principles. This analysis is critical to understand the scope of jurisprudential flexibility in modern awqāf. Design/methodology/approach The paper is an outcome of a library-based research. It uses the classical jurisprudential treatises of waqf with an aim to analyse the Sharīʿah basis of the institution, the premises of its key principles and the applied juristic analogy to derive the same. The paper covers the classical waqf books and treatises from the four Sunni schools of jurisprudence and uses a textual analysis method. Findings The paper finds that in its initial phase, the conceptual framework of waqf was not unanimously agreed by all jurists, rather its Sharīʿah permissibility remained critically disputed among them for a while. Though, the opinion of those jurists who approved the Sharīʿah-validity of waqf was to prevail in the later stage, disagreement persisted with reference to its necessary features and defining criteria. It is found that in the classical waqf literature, two most disputed aspects of waqf jurisprudence constituted the requirements for completion of a waqf and its ownership status. Research limitations/implications This study neither covers the historical contribution of waqf among the Muslim societies nor touches on the empirical aspects of modern waqf. Rather, the focus of the study is limited to analysing the classical jurisprudential discourse of waqf and distillation process of its rulings. Practical implications The objective of analysing the classical juristic discourse of waqf is to underline the premises of classical juristic analogy in determining the framework of fiqh al-awqāf (jurisprudence of waqf) in its classical permutations and to learn how to adopt a similar approach for deduction of new waqf rulings. Originality/value This paper adds original value to the body of waqf literature for analysing the classical waqf rulings distillation process along with examining the methods and mechanism of juristic analogy.
Keywords: 330